Swear(ING) ain't play(ING): The interaction of taboo language and the sociolinguistic variable. (12th September 2022) - Hunt, Matthew; Cotter, Colleen; Pearson, Hazel; Stockall, Linnaea
Abstract: Swearwords influence social evaluation of a speaker in a variety of ways depending on social context (Jay & Janschewitz (2008), The pragmatics of swearing. Journal of Politeness Research. Language, Behaviour, Culture, 4(2), 267–288). Little attention has been paid to the role of linguistic variation in social perceptions of swearing, however. This paper presents two experiments that test the role of sociolinguistic variation in the social evaluation of swearing. Experiment 1 is a variant categorization task, in which participants categorized acoustically ambiguous swearwords and phonetically matching neutral and nonwords as ending in either "‐ing" or "‐in." Results suggest that swearwords led participants to hear "‐ing" on ambiguous items. Experiment 2 is a matched‐guise task in which listeners heard a passage featuring a mix of swearwords and neutral "‐ing" words in one of four conditions: fully velar ( All‐ing ), fully alveolar ( All‐in ), only swearwords as velar ( Swear‐ing ), or only neutral words as velar ( Swear‐in ). Participants rated speakers on Likert scales (Schleef et al. (2017), Regional diversity in social perceptions of (ING). Language Variation and Change, 29(1), 29–56). Participants again displayed a tendency towards hearing "‐ing" on swearwords. As a result, responses to the Swear‐in guises were similar to those for the All‐ing guises. The consequences for our understanding of swearing, sociolinguistic perception and cognition, and style, are discussed.